Kode Etik Profesi Akuntan Publik dan Kinerja Auditor di Kantor Akuntan Publik - Sumartho, Ni Luh Ditha Usadi; Wirama, Dewa Gede; Mertha, Made; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 34 No 5 (2024), 2024)
The aim of this research is to analysis the impact of the five principles of the professional code of ethics for public accountants on the performance of auditors. The study was carried out at public accounting firms (KAP) in Bali Province. The sampling method utilized was purposive sampling, which resulted in a sample of 78 auditors from 14 KAPs. This study uses primary data collected by distribution of questionnaires. The data analysis technique used is multiple linear regression analysis. The findings show that integrity, objectivity, competence and due care, confidentiality, and professional behavior have positive effects on the performance of auditors at KAPs in Bali. Keywords: Integrity; Objectivity; Professional Competence and Due Care; Confidentiality; Professional Behavior; Auditor Performance